(untitled) (African Human Mobility Review, 2023)
This work sheds light on the still unresolved plight of statelessness in Madagascar, a country that has a long history of stateless communities, above all among the Karana people, of Indian origin and Muslim religion. In spite of several important steps undertaken to eradicate statelessness in the country (see, for example, the adoption of the 2016 Law on Nationality that partially amended the 1960 Code on Nationality), the path for the complete eradication of statelessness in the country still seems quite long. This is because of the lack of will by local authorities who seem to ignore the conditions of thousands of people, born and bred in Madagascar who, apparently for no specific reason, still do not hold Malagasy citizenship, causing them to be deprived of several basic rights that citizens are normally entitled to. In this respect, the fact that Madagascar is still not a party to several important international legal instruments adopted to eradicate statelessness, does not facilitate the situation of the thousands of stateless people in Madagascar.